Low-temperature processed, stable n-i-p perovskite solar cells with indene-C60-bisadduct as electron transport material - Omer, Mohamed I. (2022)
Organo-metallic halide perovskites (OMHP) have proven to be promising light absorbers with superb optoelectronic properties for developing the next generation of low-cost solar cells. Over the past years, the extensive research efforts on perovskite solar cells (PSCs) have led to an impressive improvement in the photovoltaic performance on many fronts and have their main field of applications in low-temperature and low power consumption photo-electronic devices, However, a wide range of highly performing PSCs structures involves the use of metal oxide electron transport materials (ETMs) such as TiO2 which requires high processing temperature that could result in a higher manufacturing energy input and cost. This also could hinder the development of low-cost and low-temperature scalable processes for device fabrication on rigid or flexible substrates. Here, we develop a low-temperature procedure (below 100 °C) that make use of Indene-C60 Bisadduct (ICBA) as an alternative ETM in the planar n-i-p-structured PSCs. After modifying the ICBA layer, we not only improved the optimum performance and stability of the device, but also study its influence on the device operation using impedance spectroscopy, and finally achieved a stabilized power conversion efficiency of 13.5%. Thereby, this study will establish low-temperature ETM as an outstanding candidate for future high stability PSCs production due to its high performance, low process temperature and easy fabrication.